2001
DOI: 10.1128/iai.69.10.6527-6531.2001
|View full text |Cite
|
Sign up to set email alerts
|

Restriction ofToxoplasma gondiiGrowth in Human Brain Microvascular Endothelial Cells by Activation of Indoleamine 2,3-Dioxygenase

Abstract: One of the first steps in the development of cerebral toxoplasmosis is the penetration of the blood-brain barrier, which is comprised of microvascular endothelial cells. We examined the capacity of human brain microvascular endothelial cells (HBMEC) to interact with Toxoplasma gondii. We found that stimulation of HBMEC with gamma interferon (IFN-␥) resulted in the induction of toxoplasmostasis. The capacity of HBMEC to restrict Toxoplasma growth after IFN-␥ stimulation was enhanced in the presence of tumor nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 25 publications
0
74
1
Order By: Relevance
“…Additionally, we have recently shown that human astrocytoma cells exhibit strong IDO activation after stimulation with IFN-␥ (12). There is an increasing body of evidence indicating that IDO activation in human cells is a potent antiparasitic and antibacterial effector mechanism (7,9,10,11,27,33,39). That viruses are also controlled by IDO activation in human cells was first indicated by Bogdahi et al in 1999 (3).…”
Section: Gamma Interferon (Ifn-mentioning
confidence: 99%
“…Additionally, we have recently shown that human astrocytoma cells exhibit strong IDO activation after stimulation with IFN-␥ (12). There is an increasing body of evidence indicating that IDO activation in human cells is a potent antiparasitic and antibacterial effector mechanism (7,9,10,11,27,33,39). That viruses are also controlled by IDO activation in human cells was first indicated by Bogdahi et al in 1999 (3).…”
Section: Gamma Interferon (Ifn-mentioning
confidence: 99%
“…Standard Western blot analysis for IDO protein expression was performed. 18 IDO enzyme activity following IFN-␥ stimulation of MSCs was measured by tryptophan-to-kynurenine conversion with photometric determination of kynurenine concentration in the supernatant as the readout. 19 In addition, IDO activity was quantified in MSC/MLR cocultures.…”
Section: Detection Of Ido Expression and Activitymentioning
confidence: 99%
“…TNF␣ increases in vitro the number of cysts formed in human fibroblasts, involving the activity of an acidic sphingomyelinase (8). TNF␣ acts synergistically with IFN␥ against cerebral toxoplasmosis by inducing indoleamine 2,3-dioxygenase activity, which degrades tryptophan, resulting in an antiparasitic mechanism in brain cells (9,10). Acute toxoplasmosis that causes rapid death in mice is accompanied by high levels of type 1 cytokines in the serum, including IFN␥ and TNF␣ (11).…”
mentioning
confidence: 99%